Curve progression in non-surgically treated patients with idiopathic scoliosis: a cohort study with 40-year follow-up - Casper Dragsted; Lærke Ragborg; Søren Ohrt-Nisse; Thomas Andersen; Martin Gehrchen; Benny Dahl (Acta Orthopaedica)
Background and purpose: Treatment of idiopathic scoliosis in childhood aims to prevent curve progression. It is generally accepted that curves > 50° have the highest risk of progression, but less well described is what happens with mild to moderate curves. The aim of this study was to assess long-term curve progression and health-related quality of life (HRQoL) and compare thoracic and thoracolumbar/lumbar (TL/L) curves. Methods: We identified 177 patients diagnosed with a pediatric spinal deformity and treated at our institution from 1972 through 1983. 91 of 129 eligible patients with idiopathic scoliosis completed follow-up (71%). Patient files from treatment/observation in childhood were reviewed including detailed descriptions of radiographs. At follow-up we assessed long standing full-spine radiographs and HRQoL with the Scoliosis Research Society 22 revised questionnaire. Results: Mean follow-up was 41 years (standard deviation [SD] 2.5 years). 21 patients underwent surgery in adolescence or early adulthood leaving 70 patients for analysis of curve progression, of whom 61 had complete radiographs. For patients with a main curve < 25° at the end of treatment in adolescence (n = 19) mean curve progression was 7° (SD 9); for 25–40° curves (n = 26) 16° (SD 13); for 40–50° curves (n =10) 22° (SD 8); and for curves > 50° (n = 6) 17° (SD 6). There was a linear association between main curve size at follow-up and SRS-22r subtotal score (P = 0.003). Conclusion: We found substantial curve progression for patients with main curves > 25° at end of treatment, but with a considerable variation between patients. Curve progression was not associated with curve size at the end of treatment and did not differ significantly between thoracic and TL/L curves. Larger main curve size at follow-up was associated with lower HRQoL.